2019
DOI: 10.1016/j.jtcvs.2018.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Educational research and training innovation in cardiothoracic surgery: A year in review

Abstract: , it has been an exciting year for the field. However, this volume of research renders it difficult to keep abreast with the latest innovations in education. This year alone in CT surgery, there were 35 education-focused abstracts, 24 sessions oriented toward emerging technology, and more than 180 sessions devoted to surgical skills and simulations. Many studies explored the role of technology-based tools in augmenting CT surgery training. These were applied to the field broadly, within subspecialties, and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Training in cardiac surgery and in congenital heart surgery requires enormous technical skills, which are acquired only with repeated procedures 14 . This is generally not possible in the operating room because of the limited possibilities available to young surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training in cardiac surgery and in congenital heart surgery requires enormous technical skills, which are acquired only with repeated procedures 14 . This is generally not possible in the operating room because of the limited possibilities available to young surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Two different types of programs have been only with repeated procedures. 14 This is generally not possible in the operating room because of the limited possibilities available to young surgeons. The ability to practice outside the operating room can improve surgical technique and enhance the learning of residents in a cardiac surgery training program.…”
Section: Training Program Developmentmentioning
confidence: 99%
“…This scenario is no longer future, it is happening now and with solid signs of growth and application also in cases of medium risk in younger patients (below 60 years of age) with promising results. New technologies in full development are signaling the need for surgeons with a new training profile [ 17 , 18 ] . In recent data from the SBCCV, it was found that 55% of Brazilian cardiovascular surgeons in activity are over 60 years of age.…”
Section: The Perspectives Of the Specialtymentioning
confidence: 99%
“…An important law of life determines that survival is not the preserve of the strongest, but of those who have the greatest capacity to adapt. It will be essential to become competent in the execution of these new procedures based on new technologies [ 18 , 19 ] . This will require more training time of one to two years invested in the subspecialties of cardiovascular surgery after completion of residency [ 15 ] .…”
Section: The Challenges Of New Surgeonsmentioning
confidence: 99%
“…Similar to these studies, Fu (2018), Hughes et al (2019) and Li et al (2018) also underlined the significance of this issue. In addition, Hunt et al (2019), López‐García et al (2019) and Mohan, Strobl, and Watson (2018) stated that providing the necessary training to staff will increase the success of this process. Also, García‐González and Ramírez‐Montoya (2019), Gómez, Zabala‐Iturriagagoitia, and Larrakoetxea (2018) and Nan (2019) and also reached the similar conclusions in their studies.…”
Section: Literature Reviewmentioning
confidence: 99%